Participation of Italian Cancer Centres of the Alleanza Contro Il Cancro (ACC) in the Organisation of European Cancer Institutes (OECI) Accreditation and Designation Program: A Successful First National Initiative. (December 2015) - Oberst, Simon; Boomsma, Femke; Lombardo, Claudio; Docter, Marjet; Blaauwgeers, Harriët; De Paoli, Paolo; de Valeriola, Dominique; Paradiso, Angelo; Saghatchian, Mahasti
The Organisation of European Cancer Institutes (OECI) launched a program for accreditation and designation (A&D) of cancer centers in Europe based on voluntary participation in 2008. In 2012, the Italian Ministry of Health decided to fund cancer centers in Italy, members of the Alleanza Contro il Cancro (ACC), to go through the OECI accreditation program. Ten centers participated in the program and 10 completed the full cycle of the OECI A&D process in consecutive series over a 2-year period. The process was successfully completed within the planned timeline and the overall findings were presented to the Italian Ministry of Health and representatives of all the participating centers in November 2015. The program had a considerable team-building effect, which will likely continue as the improvement plans are implemented. Centers fed back to OECI that the A&D program had led to better formal organization of multidisciplinary teams (MDTs) and cancer care pathways, and had helped them to harmonize the integration of research into clinical practice. Centers also concluded that they benefited from recognition through an international accreditation system, and that it had led to them developing better patient information and involvement. The importance of the improvement plans that each center had to produce following the audit reviews cannot be underestimated. The OECI concludes that implementation of the A&D program at the national level is feasible despite national peculiarities related to health planning and organization in each member state. This is a good example of an EU project working well, with member states helping each other and learning from best practice, to improve the overall quality of cancer care and research and to establish consistency. The initial accreditation is the first part of an ongoing process of improving comprehensive cancer care, integrating bench to bedside.